A primer of Italian fascism - Schnapp, Jeffrey T. (Jeffrey Thompson), 1954-; Sears, Olivia E.; Stampino, Maria Galli (Lincoln ; London : University of Nebraska Press, 2000)
A Primer of Italian Fascism makes available for the first time in English translation the key documents pertaining to one of our century’s defining mass political movements. Whereas existing anthologies survey Fascist writings in a multiplicity of national settings, A Primer of Italian Fascism opts for a tightly focused, in-depth approach that emphasizes the development of Fascist ideology in the country of its birth.
Historically speaking, Italian Fascism was the original Fascism. The model for subsequent movements including Nazism, Falangism, and Integralism, Italian Fascism set out to define a “third way” to modernization known as “corporatism.” A Primer of Italian Fascism situates the rise and fall of corporatist ideals within the framework of the actual history of Mussolini’s movement and regime. It includes not only classic doctrinal statements such as Mussolini’s “Foundations and Doctrine of Fascism” and writings by corporatist theorists such as Bottai, Pellizzi, Rocco, and Spirito, but also an array of fundamental political and juridical documents, including the party platforms adopted by the Fascist combat brigades, the 1938 Manifesto of Race, the 1940 Manifesto of Verona, and the Fascist labor and school charters. By making available such an extensive array of source texts, A Primer of Italian Fascism aims to open up for the English reader a more complex and complete vision of Fascism, both in Italy and beyond.
Includes bibliographical references (p. [319]-320) and index.
The Roger Griffin ComFas Collection
Keywords: Fascism -- Italy -- History -- Sources; Italy -- Politics and government -- 1922-1945 -- Sources